Further records and opinions (Proceedings of the Society of Antiquaries of Scotland, 1980)
Reviews some significant contributions to Scottish archaeology which appeared in this periodical in the years 1930-71 and notes changes in methodology and presentation over time. Individual topics (eg chambered cairns, Roman antiquities, castles) are traced with a simple numerical analysis of numbers of articles.